2008
DOI: 10.1242/jeb.019133
|View full text |Cite
|
Sign up to set email alerts
|

Methyl farnesoate couples environmental changes to testicular development in the crabCarcinus maenas

Abstract: SUMMARYCarcinus maenas males have two major color phases. Green-phase males molt frequently and tend to live in brackish estuaries during the summer. After becoming red-phase males, they molt infrequently, have higher mating success, and live in cooler, deeper water. We found profound differences between these two phases in the way salinity and temperature affect hemolymph levels of methyl farnesoate (MF), a hormone that affects crustacean reproduction. Few green-phase males (<10%) had detectable MF in 33 ppt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…did not increase its hemolymph levels of MF (Henry and Borst, 2005). Similar results were also observed in green phase crabs when they were treated with low saline water at 11°C (Nagaraju and Borst, 2008). Olmstead and LeBlanc (Olmstead and LeBlanc, 2007) found that environmental factors can cause aberrant sex determination via perturbations in MF signaling in D. magna.…”
Section: Effects Of Environmental Factors On Hormone Levels and Reprosupporting
confidence: 60%
See 4 more Smart Citations
“…did not increase its hemolymph levels of MF (Henry and Borst, 2005). Similar results were also observed in green phase crabs when they were treated with low saline water at 11°C (Nagaraju and Borst, 2008). Olmstead and LeBlanc (Olmstead and LeBlanc, 2007) found that environmental factors can cause aberrant sex determination via perturbations in MF signaling in D. magna.…”
Section: Effects Of Environmental Factors On Hormone Levels and Reprosupporting
confidence: 60%
“…Unilaterally, ESA male P. monodon showed a significantly higher sperm count, larger sperm head diameter and longer spikes in comparison to unablated ones, but no observable changes were noted in testicular index, spermatophore weight and sperm viability (Gomes and Honculada-Primavera, 1993). We also found that the ESA of C. maenas caused testicular index to increase to 2-fold higher than that of intact green crabs (Nagaraju and Borst, 2008). These and other research studies have led to the proposal that the eyestalk contains an inhibitory factor called GIH (Fingerman, 1997a; Haihui et al, 2006;Kulkarni et al, 1984), but the structural information and molecular and cellular mechanisms remain to be elucidated.…”
Section: The Journal Of Experimental Biologysupporting
confidence: 50%
See 3 more Smart Citations